Factors for Increasing the Social Intelligence of Future Specialists in Higher Education (European Journal of Pedagogical Initiatives and Educational Practices, 2023)
The article examines the problem of increasing the social intelligence of students in technical higher education institutions. Students are given an idea about the main direction of forming their social intelligence. The laws of social intelligence are included in the educational process. The characteristic features of the modern methodical system are highlighted.